Creativity in university teaching: a bibliometric analysis of open access scientific production - González, Oscar Alberto (2025)
Introduction: Creativity is a fundamental element in higher education since it fosters innovation, the ability to solve complex problems, and critical thinking in both students and teachers, issues necessary to adapt to the changing environment that today’s world demands. Objective: To analyze the scientific production on the teaching of creativity in the university context in Web of Science (WoS) between 2014 and 2024. Methodology: The study was based on a bibliometric review in WoS, guided by the workflow for the analysis of scientific production suggested by Zupic and Carter (2015). A total of 304 papers published between 2014 and 2024 were analyzed using digital tools such as Bibliometrix and Microsoft Excel. Results: There was a steady increase in studies addressing creativity in the university context in the last 10 years. The USA, China, and Indonesia lead the countries with the most research on creativity, in contrast to the low scientific production in Latin American countries. The thematic trend is oriented towards studies on divergent thinking and intrinsic motivation. The analysis of the conceptual structure shows improvisation and university as driving themes. Discussion: The growth of scientific production on creativity in the university environment is evident; however, although it is a widely studied topic, there are still gaps that need to be addressed, especially the relationship between creativity, communication, and transversal competencies, as well as the need for studies differentiated by gender and sociocultural context.